Should associating liver partition and portal vein ligation for staged hepatectomy be applied to hepatitis B virus-related hepatocellular carcinoma patients with cirrhosis? A multi-center study. Issue 12 (December 2022) - Lv, Jia-Hui; Chen, Wei-Zhao; Li, Yi-Nan; Wang, Jin-Xiu; Fu, Yang-Kai; Zeng, Zhen-Xin; Wu, Jia-Yi; Wang, Shuang-Jia; Huang, Xiao-Xiao; Huang, Li-Ming; Huang, Rong-Fa; Wei, Yong-Gang; et al.
Abstract: Background: It is unclear whether associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) can be performed in hepatitis B virus-related hepatocellular carcinoma (HCC) patients with cirrhosis. We explored the efficacy of ALPPS in HCC patients. Methods: Data of 54 patients who underwent ALPPS between August 2014 and July 2020 at three centers were collected. Adverse factors affecting their prognosis were analyzed and subsequently compared with 184 patients who underwent transcatheter arterial chemoembolization (TACE). Results: Overall survival rates of the ALPPS group at 1, 3, and 5 years were 70.6%, 38.4%, and 31.7%, respectively; corresponding disease-free survival rates were 50.5%, 22.4%, and 19.2%, respectively. The ALPPS group had a significantly greater long-term survival rate than the TACE group (before propensity score matching, P < 0.001; after propensity score matching, P = 0.002). Multivariate analysis demonstrated that multifocal lesions (P = 0.018) and macroscopic vascular invasion (P = 0.001) were prognostic factors for HCC patients who underwent ALPPS. After the propensity score matching, the multifocal lesions (P = 0.031), macroscopic vascular invasion (P = 0.003), and treatment type (ALPPS/TACE) (P = 0.026) were the factors adversely affecting the prognosis of HCC patients. Conclusion: ALPPS was feasible in hepatitis B virus-related HCC patients with cirrhosis and resulted in better survival than TACE.